Integrated analysis of transcriptome and metabolome reveals molecular mechanisms of salt tolerance in seedlings of upland rice landrace 17SM-19 - Zhou, Longhua; Zong, Yingjie; Li, Luli; Wu, Shujun; Duan, Mingming; Lu, Ruiju; Liu, Chenghong; Chen, Zhiwei (Frontiers in Plant Science, 2022)
Salt stress is a major abiotic stress that threatens global rice production. It is particularly important to improve salt tolerance in upland rice because of its growth environment. Upland rice landrace 17SM-19 with high salt tolerance was obtained from a previous study. In this study, an integrated analysis of transcriptome and metabolome was performed to determine the responses of the rice seedling to salt stress. When treated with 100 mm NaCl, the rice seedling growth was significantly inhibited at 5 d, with inhibition first observed in shoot dry weight (SDW). Changes in potassium (K+) content were associated with changes in SDW. In omics analyses, 1,900 differentially expressed genes (DEGs) and 659 differentially abundant metabolites (DAMs) were identified at 3 d after salt stress (DAS), and 1,738 DEGs and 657 DAMs were identified at 5 DAS. Correlation analyses between DEGs and DAMs were also conducted. The results collectively indicate that salt tolerance of upland rice landrace 17SM-19 seedlings involves many molecular mechanisms, such as those involved with osmotic regulation, ion balance, and scavenging of reactive oxygen species.